2023
DOI: 10.1002/adhm.202300873
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Controllable Preparation of Iodine‐131‐Labeled Microspheres for Radioembolization Therapy of Liver Tumors

Abstract: Transcatheter arterial radioembolization (TARE) is of great significance for the treatment of advanced hepatocellular carcinoma (HCC). However, the existing radioembolic microspheres still have problems such as non‐degradability, non‐uniform size, and inability to directly monitor in vivo, which hinders the development of TARE. In this paper, a novel radioembolic agent, 131I‐labeled methacrylated gelatin microspheres (131I‐GMs), is prepared for the treatment of HCC. Water‐in‐oil (W/O) emulsion templates are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Common geometries used for microsphere preparation include T-shaped, co-flow, and flow-focused channels. Jiang et al demonstrated the successful preparation of gelatin methacrylate microspheres using a one-step microfluidic technique [ 48 ]. The method allows for precise control of fluid flow rates, resulting in uniform and reproducible microspheres.…”
Section: Polymer Microspheres Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Common geometries used for microsphere preparation include T-shaped, co-flow, and flow-focused channels. Jiang et al demonstrated the successful preparation of gelatin methacrylate microspheres using a one-step microfluidic technique [ 48 ]. The method allows for precise control of fluid flow rates, resulting in uniform and reproducible microspheres.…”
Section: Polymer Microspheres Overviewmentioning
confidence: 99%
“…Filipin proteins and sericin proteins rich in tyrosine have been used for chelating 177 Lu and 131 I, respectively [ 30 , 91 ]. GelMA, with tyrosine-rich residues, was successfully grafted onto microspheres, producing 131 I-labeled GelMA radiolabeled microspheres ( 131 I-GMs), enhancing radionuclide stability and reducing leakage [ 48 ].…”
Section: Polymer Microspheres In Cancer Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sizes of the HA microspheres prepared by stirring or spray drying methods are not uniform. Microfluidic technology, which can generate monodisperse and controllable droplets by controlling the dimensions of the device and the flow rates of fluids, can be used to fabricate monodisperse HA microspheres. Shendi et al modified HA with DVS first, reconstructed the lyophilized VS-HA hydrogel precursor in phosphate-buffered solution (PBS) containing 0.1% Irgacure 2959 (I2959) as photo-cross-linker, and then prepared VS-HA droplets by microfluidic technology and fabricated cross-linked hydrogel microspheres through free radical reaction initiated by ultraviolet light. However, this method requires the use of DVS for modifying HA, and DVS has certain toxicities that may cause side effects such as inflammation and edema in the human body. , Yuk et al dissolved HA in sodium hydroxide solution first and stirred for 48 h, then prepared HA droplets by microfluidic technology, and collected the droplets into isobutanol solution containing poly­(ethylene glycol) diglycidyl ether (PEGDE) to obtain HA microspheres through chemical cross-linking.…”
Section: Introductionmentioning
confidence: 99%